OVERCOMING OBSTACLES IN THE DEVELOPMENT OF IKRT / UMK THROUGH APPLICATION OF APPROPRIATE TECHNOLOGY - Ayu Arwati, I Gusti; Euis Nina Saparina; Nur Endah Retno Wuryandari (Dinasti Publisher, 2020)
The SME sector that has an important role in the Indonesian industry is the small and home industry (IKRT) or micro and small businesses (MSME). In everyday life, washing clothes and washing the house is an activity that is usually done by everyone, especially by the home industry. IKRT (UMK) Suradita RW 09 Suradita Indah Complex, is IKRT (UMK) in the Suradita sub-district, which produces green cleaning products guided by Universitas Mercu Buana lecturers who have been operating for one year. IKRT (UMK) was established to increase the knowledge of housewives who live in RW 09, where production is marketed in the surrounding area as well. In addition there is no good management governance, also a good marketing strategy. Based on the above, the objectives of community service are (1) using appropriate technology in the green cleaner production process, (2) improving the quality of green cleaner product formulations, (3) implementing good governance management and marketing strategies to be more effective and efficient and has sustainable competitiveness. The results of this community service are (1) appropriate technology that can be used in the production process. (2) Improving the quality of green cleaner product formulations and (3) governance management and marketing strategies. And can avoid Suradita IKRT which is more effective and efficient and has sustainable competitiveness.